Classification, association and pattern completion using neural similarity based methods - Duch, Włodzislaw; Adamczak, Rafał; Diercksen, Geerd H.F. (Zielona Góra: Uniwersytet Zielonogórski)
A framework for Similarity-Based Methods (SBMs) includes many classification models as special cases: neural networks of the Radial Basis Function type, Feature Space Mapping neurofuzzy networks based on separable transfer functions, Learning Vector Quantization, variants of the k nearest neighbor methods and several new models that may be presented in a network form. Multilayer Perceptrons (MLPs) use scalar products to compute a weighted activation of neurons, combining soft hyperplanes to provide decision borders.
Keywords: neural networks; classification; associations; pattern recognition